Analisis Tegangan pada Struktur Sasis Lowbed Trailer dengan Metode Elemen Hingga - Friska Nur Anggraeni; Mohammad Miftachul Munir; Mohamad Hakam (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
The demand for heavy equipment is rising alongside industrial growth. The 120-ton Lowbed Trailer Dolly, owned by CV. XYZ, is commonly used for transporting heavy loads. Its chassis structure is crucial for supporting the truck and cargo. Structural analysis can help determine the strength and critical points with the highest stress, as well as the necessary structural stability to withstand the applied load. To understand the stress distribution and loading conditions, theoretical calculations were performed for comparison, along with 3D modeling using two types of beams: flat and arch. Furthermore, finite element analysis was conducted using Fusion 360 software (Education License). Theoritical calculation had a stress of 149.74 MPa and the stress analysis showed the flat-type beam had a stress of 168.925 MPa (below the maximum allowable stress of 233.33 MPa), while the arch-type beam had 267.097 MPa (exceeding the maximum allowable stress). Thus, the flat-type model is considered safe for a 120ton load. The percentage error between theoretical calculations and simulation results is 11.39% for flat-type and 43.49% for arch-type models.